Associations between perfluoroalkyl compounds and immune and clinical chemistry parameters in highly exposed bottlenose dolphins (Tursiops truncatus). (22nd February 2013) - Fair, Patricia A.; Romano, Tracy; Schaefer, Adam M.; Reif, John S.; Bossart, Gregory D.; Houde, Magali; Muir, Derek; Adams, Jeff; Rice, Charles; Hulsey, Thomas C.; Peden‐Adams, Margie
Abstract Perfluoroalkyl compounds (PFCs) are ubiquitous, persistent chemical contaminants found in the environment, wildlife, and humans. Despite the widespread occurrence of PFCs, little is known about the impact these contaminants have on the health of wildlife populations. The authors investigated the relationship between PFCs (including ∑perfluorocarboxylates, ∑perfluoroalkyl sulfonates, perfluorooctane sulfonate, perfluorooctanoic acid, and perfluorodecanoic acid) and the clinocopathologic and immune parameters in a highly exposed population (n = 79) of Atlantic bottlenose dolphins (mean ∑PFCs = 1970 ng/ml; range 574–8670 ng/ml) sampled from 2003 to 2005 near Charleston, South Carolina, USA. Age‐adjusted linear regression models showed statistically significant positive associations between exposure to one or more of the PFC totals and/or individual analytes and the following immunological parameters: absolute numbers of CD2+ T cells, CD4+ helper T cells, CD19+ immature B cells, CD21+ mature B cells, CD2/CD21 ratio, MHCII+ cells, B cell proliferation, serum IgG1, granulocytic, and monocytic phagocytosis. Several PFC analyte groups were also positively associated with serum alanine aminotransferase, gamma‐glutamyltransferase, creatinine, phosphorus, amylase, and anion gap and negatively associated with cholesterol levels, creatinine phosphokinase, eosinophils, and monocytes. Based on these relationships, the authors suggest that the PFC concentrations found in Charleston dolphins may have effects on immune, hematopoietic, kidney, and liver function. The results contribute to the emerging data on PFC health effects in this first study to describe associations between PFCs and health parameters in dolphins. Environ. Toxicol. Chem. 2013;32:736–746. © 2013 SETAC